Partisipasi Kontak Kerukunan Sosial (K2S) Suku Jawa terhadap Pendidikan Masyarakat Islam Kota Kupang - Muhammad Tamrin (IAI Darussalam, 2019)
Essentially, K2S was established to be an unified forum for all Javanese in Kupang City and its surroundings. K2S was a kinship independent social organization which is not affiliated with other social political or community organizations. The main objective of K2S was to develop family relations, brotherhood, togetherness and harmonization between K2S members, maintain and develop the values of Javanese art and culture, tradition, supporting faith activities, strengthen worship, and enhance morals of K2S members based on their dogma and it was also for contributions of Kupang city development. This study was done to ascertain the efforts of K2S in improving education of Islamic community in Kupang city. In this qualitative descriptive research, the data was gathered through interviews, observation, and documentation. The data was analyzed use the interactive data analysis models by Milles and Huberman. The study showed that the Javanese social harmony intercaction (K2S) took part in: 1. Social community aspects; 2. member’s training and empowerments; 3. spirituality; 4. Arts and culture.